FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH MASUK ASURANSI PENDIDIKAN PADA AJB BUMIPUTERA 1912 CABANG SINGKAWANG - Isfiswari, Uray Gita; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of this research is to find out how the customer's interest in entering education insurance at AJB Bumiputera 1912 is based on 1) Product, 2) Promotion, 3) Price, and 4) service. The approach used in this thesis is a qualitative approach with an interactive inquiry method. Data collection techniques used are interview techniques and documentation techniques. Data collection tools are interview guides and cameras. The results of the study show (1) The education insurance product at AJB Buiputera 1912 offered to customers can help customers prepare funds to finance children's education. (2) Promotions carried out by AJB Bumiputera 1912 are only when employees/agents of AJB Bumiputera 1912 explain directly to customers the latest products available at AJB Bumiputera 1912. To increase public interest in the products owned by AJB Bumiputera 1912, more promotions need to be carried out in the media social media, for example placing advertisements on social media platforms. (3) The premium is calculated based on the type of education insurance taken, the age of the parents and the age of the child, as well as the desired length of the contract. AJB Bumiputera 1912 customers have always paid premiums on time and the premiums given by AJB Bumiputera 1912 according to their abilities. (4) AJB Bumiputera 1912 strives to provide the best service to customers, this can be seen from the services provided by agents who interact directly with customers. AJB Bumiputera customers always feel that AJB Bumiputera 1912 agents are always friendly and always provide solutions and suggestions when customers are in trouble.Keywords: Customer Interest Factors, Education Insurance, AJB Bumiputera 1912